The Comparison Between Quantum Communication and Traditional Encryption - Xu, Yixuan (Transactions on Computer Science and Intelligent Systems Research, 2025)
In recent years, as computational power increases, the traditional encryption methods are becoming increasingly vulnerable to attacks and thus have some safety issues. Therefore, the application of quantum communication has become increasingly widespread, and more technologies related to quantum communication have been invented. This article provides an overview of the differences between quantum communication and traditional encryption in terms of their advantages, disadvantages, security, and the challenges they face in applications. Indeed, the unique characteristics of quantum communication, like quantum superposition and quantum entanglement, provide quantum communication with good security. Furthermore, quantum communication has several advantages, like quantum key distribution, which ensures secure communication, high capacity, high speed, resistance to eavesdropping, and error correction. However, the traditional encryption is still widely used. The traditional encryption, which relies on mathematical algorithms and offers mature encryption methods like Advanced Encryption Standard and Rivest-Shamir-Adleman, must have advantages over quantum communication. Therefore, a comprehensive comparison between traditional encryption and quantum communication is essential to understand their respective roles in the future of secure information exchange.
Keywords: Quantum communication; traditional encryption; quantum physics.